2018
DOI: 10.1111/hdi.12674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of creatinine index and geriatric nutritional risk index for nutritional evaluation of patients with hemodialysis

Abstract: Either CI or GNRI was a valid tool for longitudinal observation of nutritional status of patients on chronic HD and facilitated the screening of cases with malnutrition. Compared with GNRI, CI ranked higher in performance for the assessment and monitoring of nutritional status in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The GNRI is correlated with the Malnutrition-Inflammation Score, which is now regarded as the gold standard for diagnosing PEW or malnutrition [22]. The modified Cr index is a marker of skeletal muscle mass and is also correlated with GNRI [23]. In the present study, our mPEW-S was significantly associated with both indexes.…”
Section: Discussionsupporting
confidence: 57%
“…The GNRI is correlated with the Malnutrition-Inflammation Score, which is now regarded as the gold standard for diagnosing PEW or malnutrition [22]. The modified Cr index is a marker of skeletal muscle mass and is also correlated with GNRI [23]. In the present study, our mPEW-S was significantly associated with both indexes.…”
Section: Discussionsupporting
confidence: 57%
“…Although the GNRI and Cr index are calculated using a different set of clinical parameters, our results suggest that they partially share nutritional information regarding the predictability of all-cause mortality. One very recent study compared the model predictability of the GNRI and Cr index regarding all-cause mortality in a relatively small cohort of 88 Chinese hemodialysis patients 21 . Results showed that model performance for all-cause mortality with the Cr index was better than that with the GNRI.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study infection-related and all-cause death predicted by the GNRI and by serum Cr were comparable, indicating that serum albumin-based surrogates and serum Cr-based surrogates are equally useful for the prediction of mortality in hemodialysis patients 24 . Both GNRI and Cr index are found to be valid tools for longitudinal observation of nutritional status in patients receiving maintenance hemodialysis 21,25 . Given that outcome predictability and nutritional information derived from the GNRI and the Cr index are comparable, the GNRI-a simpler form of nutritional surrogate-may be more useful and practical for clinical use than the Cr index in patients undergoing maintenance hemodialysis.…”
Section: Adjusted Odds Ratio (95% Ci) For a Low Cr Index Category P-vmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of poor nutritional status of patients with CKD is even considered as the leading cause of poor clinical outcomes and quality of life and mortality [6,7]. Several studies assessing the nutritional status of patients with CKD, using methods such as anthropometric assessments and biochemical evaluation, have shown a positive correlation with mortality [17][18][19].…”
Section: Introductionmentioning
confidence: 99%